A Program of Moderate Physical Training for Wistar Rats Based on Maximal Oxygen Consumption - Leandro, Carol Góis; Levada, Adriana Cristina; Hirabara, Sandro Massao; Manhães-de-Castro, Raul; De-Castro, Célia Barbosa; Curi, Rui; Pithon-Curi, Tânia Cristina (Journal of strength and conditioning research, 2007)
Moderate physical training is often associated with improved cardiorespiratory fitness in athletes and the general population. In animals, studies are designed to investigate basic physiology that could be invasive and uncomfortable for humans. The standardization of an exercise training protocol for rats based on maximal consumption of oxygen (VO(2)max) is needed. This study validated a program of moderate physical training for Wistar rats based on VO(2)max determined once a week. A 10-stage treadmill running test was developed to measure VO(2)max through an indirect, open circuit calorimeter. Thirty male Wistar rats (210-226 g) were randomly assigned to either a nontrained group or a trained group. The animals were evaluated weekly to follow their VO(2)max during 8 weeks of moderate training and to adjust the intensity of the protocol of training. The soleus muscle was removed for determination of citrate synthase activity. Trained animals maintained their values of VO(2)max during a moderate running training and showed a significant less body weight gain. An increase of 42% in citrate synthase activity of the soleus muscle from trained rats was found after the training program. Our study presents a protocol of moderate physical training for Wistar rats based on VO(2)max. Peripheral adaptations such as the values of citrate synthase activity also responded to the moderate training program imposed as observed for VO(2)max. Other studies can use our protocol of moderate training to study the physiologic adaptations underlying this specific intensity of training. It will provide support for study with humans.